Use-Based Pricing and Prepaid-Based Pricing for Service Products: Analysis of an Unlimited Prepaid Card - Chuan Zhang (IEEE Access, 2018)
This paper analyses the optimal pricing strategies of two sales models for a service product: the use-based mode, in which a customer pays for each use, and the prepaid-based mode, in which a customer enjoys a service with a card that represents an up-front payment for a period of time. For the prepaid mode, we analyze a kind of unlimited card, such as a fitness card. With considerations of customers' perceived value, transfer fees and the time-value of the funds, we establish generalized pricing models of a service product under these two sales modes in a monopoly, and discuss the pricing strategies between two companies using game theory in a duopoly. Research shows that in a monopoly, the optimal use-based price is identical whether the transfer fee exists or not, and the optimal prepaid-based price when the transfer fee exists is lower than when it does not exist. In a duopoly, according to game theory, we can derive two Nash equilibria from nine situations. Finally, through numerical examples, we verify the effectiveness of the pricing strategy and derive some managerial insights.